2015
DOI: 10.1002/pbc.25554
|View full text |Cite
|
Sign up to set email alerts
|

Successful hematopoietic cell transplantation in a patient with X‐linked agammaglobulinemia and acute myeloid leukemia

Abstract: X-linked agammaglobulinemia (XLA) is a primary immunodeficiency characterized by marked reduction in all classes of serum immunoglobulins and the near absence of mature CD19+ B-cells. Although malignancy has been observed in patients with XLA, we present the first reported case of acute myeloid leukemia (AML) in a patient with XLA. We also demonstrate the complete correction of the XLA phenotype following allogeneic hematopoietic cell transplantation for treatment of the patient’s leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…An early series of 6 patients failed to demonstrate engraftment in the absence of myeloablative conditioning (10). Table 2 summarizes 3 subsequent allograft cases, including the patient in this manuscript, in which conditioning resulted in high levels of sustained donor engraftment, restoration of B-cell numbers and detectable antibody levels (11, 12). In Case 1, total Ig levels post-transplant were reported to be normal, as were responses to vaccination, but no details were given for IgA and IgM levels (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early series of 6 patients failed to demonstrate engraftment in the absence of myeloablative conditioning (10). Table 2 summarizes 3 subsequent allograft cases, including the patient in this manuscript, in which conditioning resulted in high levels of sustained donor engraftment, restoration of B-cell numbers and detectable antibody levels (11, 12). In Case 1, total Ig levels post-transplant were reported to be normal, as were responses to vaccination, but no details were given for IgA and IgM levels (11).…”
Section: Discussionmentioning
confidence: 99%
“…Initial attempts of alloSCT without conditioning resulted in failed engraftment in 6 XLA patients (10). Since then, two XLA patients were treated with allograft with conditioning: full myeloablation in a 13 yr-old XLA with acute myeloid leukemia (11), and reduced conditioning in 28 yr-old XLA with recurrent serious infections in spite of IgRT (12). Both cases demonstrated alloSCT provided at least partial reconstitution of antibody levels and responses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to xid , stable donor engraftment was not achieved in human cases, and resulted in no harm, but to no benefit. Abu-Arja et al recently reported successful allo-SCT in a patient with XLA and AML, in which they used a myeloablative conditioning regimen because it is the standard treatment for AML [ 7 ]. They suggested the use of a RIC regimen in the case of allo-SCT for XLA.…”
Section: Case Presentationmentioning
confidence: 99%
“…They did not use a preconditioning regimen based on findings obtained in XLA model mice, in which no stable donor engraftment was achieved, resulting in no harm, but no benefit [ 6 ]. Allo-SCT was recently performed on a patient with XLA coincidentally complicated with acute myeloid leukemia (AML), in which a myeloablative conditioning regimen was used because it is the standard treatment for AML [ 7 ]. Since XLA itself is a non-malignant disorder, reduced intensity conditioning (RIC) may be suitable for cases of allo-SCT for XLA in order to minimize transplantation-associated toxicity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, two XLA patients were successfully transplanted with matched donor hematopoietic stem cells. One, a 13‐year‐old male with known XLA and newly diagnosed acute myeloid leukemia, was transplanted following myelo‐ablative conditioning (Abu‐Arja et al, ). The other, a 28‐year‐old male with XLA and recurrent life‐threatening infections, received a matched sibling transplant following reduced intensity conditioning (Ikegame et al, ).…”
Section: Introductionmentioning
confidence: 99%